Contribution of ion reflection to the energy budgets of dipolarization fronts. Issue 2 (16th January 2016) - Li, Jia‐Zheng; Zhou, Xu‐Zhi; Angelopoulos, Vassilis; Liu, Jiang; Runov, Andrei; Pan, Dong‐Xiao; Zong, Qiu‐Gang
Abstract: Dipolarization fronts, earthward propagating structures in the Earth's magnetotail characterized by sharp enhancements of the northward magnetic field, are important sites of energy conversion from electromagnetic to particle energy. The large energy conversion rate observed at these fronts suggests significant particle acceleration and heating, which powers the ambient current sheet to generate plasma flows in the magnetotail plasma sheet and its boundary layer. Using a simple model of ion reflection at the dipolarization front, we estimate ion energy enhancement in the ambient plasma sheet and find it to be comparable with typical electromagnetic energy converted at the front. Validated by dipolarization front statistics from THEMIS (Time History of Events and Macroscale Interactions during Substorms) observations, this result suggests the important contribution of ion reflection to the energy budgets of dipolarization fronts during their earthward propagation. Key Points: Dipolarization fronts are key sites of energy conversion from electromagnetic to particle energy Ion reflection contributes significantly to the energy conversion at dipolarization fronts Dipolarization front current is largely carried by ions previously in the ambient plasma sheet